Hubungan Pengetahuan dan Sikap Ibu dengan Upaya Pencegahan Stunting pada Balita di Wilayah Kerja Puskesmas Simpang Kawat Kota Jambi - Sri Arnita; Dwi Yunita Rahmadhani; Mila Triana Sari (Jurnal Akademika Baiturrahim Jambi, 2020)
Stunting is a condition in which an toddler has a length and heights are less when compared with age caused by multidimensional factors, namely poor nutritional factors experienced by toddlers, lack of maternal knowledge about health and nutrition, impact on the level of intelligence, susceptibility to disease. This study aimed to determine the correlation of knowledge and mother’s attitude with stunting prevention efforts in toddlers. This is quantitative research by using cross sectional design; it was conducted at the public health center Simpang Kawat Jambi city from February until July 2019. Populations were 881 people with total samples were 87 mother. The sample used proportional random sampling, analyzed as univariate and bivariate by using chi-square test. The findings indicated that from 87 mother, most of the mother (67.8%) have good stunting prevention efforts, most of the mother (65.5%) have high knowledge, most of the mother (64.4%) have good attitude. The result of this study were obtained there is significant correlation between knowledge with stunting prevention efforts in infants where p-value = 0.373 (p>0.05). There is significant correlation between attitude with stunting prevention efforts in toddlers where p-value = 0.030 (p<0.05). It is expected to the public health center Simpang Kawat to stunting prevention efforts carried out primary prevention through health promotion in providing understanding about stunting so that a change of attitude which is expected in achieve optimal health.